Nanoengineered composite defog coating - YANG ARTHUR J; ZHANG RUIYUN (2013)
An engineered nano-composite coating may include hydrophobic an hydrophilic domains, may be applied to transparent and non-transparent substrates using a continuous process, may be UV curable and may impart antifogging characteristics to the substrate.